Copper oxide nanoparticles as contrast agents for MRI and ultrasound dual-modality imaging. (10th July 2015) - Perlman, Or; Weitz, Iris S; Azhari, Haim
Abstract: Multimodal medical imaging is gaining increased popularity in the clinic. This stems from the fact that data acquired from different physical phenomena may provide complementary information resulting in a more comprehensive picture of the pathological state. In this context, nano-sized contrast agents may augment the potential sensitivity of each imaging modality and allow targeted visualization of physiological points of interest (e.g. tumours). In this study, 7 nm copper oxide nanoparticles (CuO NPs) were synthesized and characterized. Then, in vitro and phantom specimens containing CuO NPs ranging from 2.4 to 320  μ g · mL −1 were scanned, using both 9.4 T MRI and through-transmission ultrasonic imaging. The results show that the CuO NPs induce shortening of the magnetic T1 relaxation time on the one hand, and increase the speed of sound and ultrasonic attenuation coefficient on the other. Moreover, these visible changes are NP concentration-dependent. The change in the physical properties resulted in a substantial increase in the contrast-to-noise ratio (3.4–6.8 in ultrasound and 1.2–19.3 in MRI). In conclusion, CuO NPs are excellent candidates for MRI-ultrasound dual imaging contrast agents. They offer radiation-free high spatial resolution scans by MRI, and cost-effective high temporal resolution scans by ultrasound.